Cranial Ewing Sarcoma/Peripheral Primitive Neuroectodermal Tumors: A Retrospective Study Focused on Prognostic Factors and Long-Term Outcomes - Chen, Jun; Cheng, Ruimin; Fan, Fanfan; Zheng, Yifeng; Li, Yakun; Chen, Yong; Wang, Yu (Frontiers in Oncology, 2019)
Purpose: Cranial Ewing sarcoma (ES)/peripheral primitive neuroectodermal tumors (pPNETs) are rarely reported because of their extremely low incidence, and the current understanding of these tumors is poor. The purpose of this study was to illustrate the clinical, radiological, and pathological features of cranial ES/pPNETs and to discuss prognostic factors by survival analysis. Methods: A total of 31 patients who were pathologically diagnosed with cranial ES/pPNETs between 2000 and 2019 were enrolled in this study. To identify which parameters were associated with higher progression-free survival (PFS) and overall survival (OS) rates, univariate and multivariate analyses were performed. Results: The mean follow-up period was 24.8 months (range, 1–109 months). Eighteen (58.1%) patients had local recurrence and seven (22.6%) patients had distant metastasis. The results of the univariate analysis suggest that the extent of resection and adjuvant radiotherapy are potential prognostic factors for PFS and OS. Adjuvant chemotherapy was associated with OS (P = 0.027) but not with PFS (P = 0.053). The multivariate analysis revealed that the extent of resection and adjuvant radiotherapy were independent prognostic factors for both PFS and OS. In addition, metastasis was an adverse prognostic factor for OS. Conclusions: Surgical management plays a crucial role in the treatment of cranial ES/pPNETs, and gross total resection should be striven for whenever possible. Postoperative radiotherapy is highly recommended to improve PFS and OS. This study also confirms that metastasis is an adverse prognostic factor for cranial ES/pPNETs.